Resenha de: The Statistical History of the United States from the Colonial Times to the present - Bresciani, M. Stella (Revista de História, 1969)
The Statistical History of the United States from the Colonial Times to the Present, Fairfield Publishers, Inc., Stamford, Connecticut, U. S. A..